Effects of Supplemental Feeding on Northern Bobwhite Populations in South Texas - Ted B. Doerr; Nova J. Silvy (National Quail Symposium Proceedings, 2017)
During 1985–87, the effects of supplemental feeding on northern bobwhite (Colinus virginianus) populations were studied on 4 paired sites, representing a cross-section of soils, vegetation, and hunting pressure in south Texas. Whole milo was provided from late fall–March. Feeding increased winter survival of birds on deep sand sites (225–245%), but not on red sandy loam or clay sites. Feeding did not improve reproductive success on any of the study sites. Most birds collected had milo in their crops and there was a tendency to find birds close to feeders more often than at random points. The study demonstrated that supplemental feeding can increase survival if food is limiting, however, data suggested feeding was not effective when habitat structure was inappropriate, or when food was not limiting.
Keywords: Colinus virginianus; northern bobwhite; reproduction; supplemental feeding; survival; Texas